Antifungal Activity of 5-Fluorouridine Against Candida albicans and Candida parapsilosis Based on Virulence Reduction - Ewa Lenarczyk; Damian Oleksiak; Monika Janeczko (Molecules)
This study aims to explore the potential repurposing of 5-fluorouridine (5-FUrd) as an antifungal agent against Candida species. We evaluated the responses of nine reference species of Candida spp. and one hundred clinical isolates of C. albicans to 5-FUrd using the broth microdilution method. Additionally, we assessed the effect of 5-FUrd on selected virulence factors, including biofilm formation, cell adhesion, dimorphism, hydrolase secretion, and hemolytic activity, in the two most sensitive Candida species, C. albicans and C. parapsilosis. The frequency of spontaneous mutations occurring in these two Candida species under the influence of 5-FUrd was also determined. Finally, we examined the cytotoxic properties of 5-FUrd against human erythrocytes and zebrafish embryos. Our results demonstrated that 5-FUrd exhibits antifungal activity in vitro, inhibits biofilm formation, suppresses hyphal growth, reduces cell surface hydrophobicity, eradicates mature biofilms, and decreases the secretion of extracellular proteinases and hemolytic activity in C. albicans and C. parapsilosis cells. The overall mutation frequency under the selective pressure of 5-FUrd ranged from 2 × 10−5 to 1.2 × 10−4 per species. Notably, the exposure to 5-FUrd did not induce significant toxic effects on human erythrocytes or zebrafish embryos. This study highlights the potential clinical application of 5-FUrd as an anti-Candida agent.